2015
DOI: 10.1007/s00429-015-1046-3
|View full text |Cite|
|
Sign up to set email alerts
|

Neurons in the lateral part of the lumbar spinal cord show distinct novel axon trajectories and are excited by short propriospinal ascending inputs

Abstract: Order of Authors Secondary Information:The role of spinal dorsal horn propriospinal connections in nociceptive processing is not yet established. Recently described, rostrocaudally oriented axon collaterals of lamina I projection and local-circuit neurons (PNs and LCNs) running in the dorsolateral funiculus (DLF) may serve as the anatomical substrate for intersegmental processing. Putative targets of these axons include lateral dendrites of superficial dorsal horn neurons, including PNs, and also neurons in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…The membranous expression of the YFP-channelrhodopsin fusion protein in the Phox2a::Cre;Rosa26 LSL-ChR2-YFP mice allowed clear visualisation of dendritic spines, and also of Homer puncta in both dendritic spines and shafts. There have apparently been few reports of dendritic spines on lamina I projection neurons, although Antal et al 41 examined 5 lamina I projection neurons and found a mean spine density of 5/100 μm, which is consistent with the present result. We found that all of the cells possessed dendritic spines, although the mean density (6.3 spines/100 μm of dendrite) was considerably www.nature.com/scientificreports/ lower than that on some other neurons in the superficial dorsal horn, since we have reported values of 17-19 spines/100 μm for excitatory interneurons with substance P or that express green fluorescent protein (GFP) in the transgenic GRP::eGFP line 42 .…”
Section: Dendritic Spines and Excitatory Synaptic Inputssupporting
confidence: 91%
“…The membranous expression of the YFP-channelrhodopsin fusion protein in the Phox2a::Cre;Rosa26 LSL-ChR2-YFP mice allowed clear visualisation of dendritic spines, and also of Homer puncta in both dendritic spines and shafts. There have apparently been few reports of dendritic spines on lamina I projection neurons, although Antal et al 41 examined 5 lamina I projection neurons and found a mean spine density of 5/100 μm, which is consistent with the present result. We found that all of the cells possessed dendritic spines, although the mean density (6.3 spines/100 μm of dendrite) was considerably www.nature.com/scientificreports/ lower than that on some other neurons in the superficial dorsal horn, since we have reported values of 17-19 spines/100 μm for excitatory interneurons with substance P or that express green fluorescent protein (GFP) in the transgenic GRP::eGFP line 42 .…”
Section: Dendritic Spines and Excitatory Synaptic Inputssupporting
confidence: 91%
“…For example, when the diaphragm is irritated by air in the peritoneum, or by inflammation of the gallbladder, the patient complains of shoulder pain (C3‐4‐5), or with angina, left arm pain (T1). The same phenomenon occurs when neurons within lamina I receive input from lower lumbar nerves and integrate this information with the muscles and joints (63, 96). Somatic and visceral C‐fibers also converge onto the same neurons in the lamina II; therefore, C‐fibers of different origin can inhibit each other (32).…”
Section: T12 Drg‐s For Axial Lbp: Integrating the Evidencementioning
confidence: 90%
“…In some cases, C‐fiber pain may ascend up to as many as six segments in LT (46, 48, 56, 59–62). This is the anatomical substrate for intersegmental processing (63). Once in the DH, the nociceptors synapse in Rexed laminae I and II of the gray matter, the posteromarginal nucleus and the substantia gelatinosa (30, 46–48), and from there they synapse on second‐order neurons.…”
Section: Anatomy and Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…). In support of this, morphological analysis of DLF neurons by single‐cell labeling demonstrated the presence of several subtypes of long‐range neurons with distinct axonal trajectories (Antal et al ., ). Only a few cells in the DLF were EdU‐positive ones in mice treated with EdU later than E10.5 (Fig.…”
Section: Discussionmentioning
confidence: 97%